The Siberian dilemma [compact disc, unabridged] - Smith, Martin Cruz, 1942- (Smith, Martin Cruz, 1942- Arkady Renko novel., 2019)
Journalist Tatiana Petrovna is on the move. Arkady Renko, an iconic Moscow investigator, and Tatiana's part-time lover hasn't seen her since she left on assignment over a month ago. When she doesn't arrive on her scheduled train, he's positive something is wrong. No one else thinks Renko should be worried, Tatiana is known to disappear during deep assignments, but he knows her enemies all too well and the criminal lengths they'll go to keep her quiet. Renko embarks on a dangerous journey to find Tatiana and bring her back.